ETHICS FOR PEOPLE WHO WORK IN TECH. - Steen, Marc. ([Place of publication not identified] : CHAPMAN & HALL CRC, 2022)
This book is for people who work in the tech industry--computer and data scientists, software developers and engineers, designers, and people in business, marketing or management roles. It is also for people who are involved in the procurement and deployment of advanced applications, algorithms, and AI systems, and in policy making. Together, they create the digital products, services, and systems that shape our societies and daily lives. The book's aim is to empower people to take responsibility, to upgrade' their skills for ethical reflection, inquiry, and deliberation. It introduces ethics in an accessible manner with practical examples, outlines of different ethical traditions, and practice-oriented methods. Additional online resources are available at: ethicsforpeoplewhoworkintech.com.
13. Relationships and care -- 14. A social media app -- 15. Virtues and flourishing -- Part III: Methods to integrate ethics -- 16. Methods to 'do ethics' in your project -- 17. Human-Centred Design -- 18. Value Sensitive Design -- 19. Responsible Innovation -- 20. What does your next project look like? -- 21. Exemplars -- Notes and further reading -- Gratitude -- About the author -- Index
OCLC-licensed vendor bibliographic record.
Keywords: Computer science -- Moral and ethical aspects; Information technology -- Moral and ethical aspects; Computer scientists -- Professional ethics; BUSINESS & ECONOMICS / Business Ethics; BUSINESS & ECONOMICS / Statistics; COMPUTERS / General